ANALISIS DAMPAK TRANSFER PEMERINTAH TERHADAP KINERJA FISKAL DI KABUPATEN/KOTA PROPINSI JAWA TENGAH DALAM PELAKSANAAN DESENTRALISASI FISKAL - Sasana, Hadi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2006)
In the regional autonomy era, city or district have to be able to increase their own income to fund their government affairs. Realization of a more realistic regional autonomy can offer tangible economic, social and political benefits to the region. This paper analyze the influence of central government transfer, Gross Regional Domestic Product (GRDP) per capita, consumer price index to original regional income (PAD), and the influence of central government transfer, PDRB per capita, population to routine and regional development expenditure. Data panels of all districts and cities (29 districts and 6 cities) since 2001 up to 2004 are used and the analyzing instrument used by pooled data with fixed effect model.The result of the study shown that central government transfer and the GRDP per capita positive and significant influence to the PAD, routine and regional development expenditure.Consumer price index has positive and significant influence to the PAD, and the total population only has positive and significant influence to the routine expenditure and has nothing to do with development expenditure.